Breeding Methods for Antrachnose Resistant Chili Pepper in the Last Decade: A Review - Putra, Fitriansyah; Carsono, Nono; Widiantini, Fitri; Bakti, Citra; Mitalo, Oscar W.; Kang, Seung Won (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Chili is one of the most economically valuable commodities cultivated worldwide. The high interest in chili can be attributed to capsaicin, which provides a spicy sensation when consumed. The level of interest in chili cultivation does not necessarily correlate with the yields obtained. The loss in production and yield can be attributed to the disruption of the Colletotrichum spp., which causes anthracnose disease. Breeding for anthracnose-resistant chili has been a focus of research for many scientists in various countries. Conventional and molecular methods are employed in the production of anthracnose-resistant chilies. This study will examine a range of articles and investigate the development of anthracnose-resistant chilies. The article was searched in the Scopus database. The articles were filtered based on the publication date range of 2014 to 2024, resulting in 343 articles. Furthermore, the articles were evaluated based on predetermined criteria, resulting in the identification of 22 articles. The breeding of anthracnose-resistant chili plants employs a range of conventional and molecular techniques to identify the most suitable lines. Various techniques, including crossing and different kinds of selection, were employed and validated through the development of molecular markers. Markers and genes have been identified, including RA80f6_r1, RA80f6_g1, RA80f6_g2, and RCT1, which are responsible for anthracnose resistance. This review provides an overview of the various anthracnose-resistant chili breeding methods.